Partial cognitive functions affecting reading method of pupils with mild intellectual disabilities - Ďorďovičová, Jana; Hlebová, Bibiána; Palková, Veronika (Journal of Exceptional People, 2015)
This paper deals with the analysis of reading method (syllables reading and fluent reading) and the level of partial cognitive functions of pupils with mild intellectual disabilities educated in terms of school integration in elementary school. To identify pupils' performance in reading competence (reading method) we used pedagogical diagnostics of reading of younger students as a research tool (Čižmarovič, Kalná 1991). For detecting the level of partial cognitive functions we applied a research tool called T-254 deficits of partial functions (Sindelarová, adapted Černý 2008). Moreover, 46 four-grade students (20 girls, 26 boys) aged 10–12 years attending the elementary school in the Prešov region, were involved in testing. Monitored dependent variables were: partial cognitive functions and independent variables included: methods of reading – reading syllables, fluent reading. Through the analysis of the collected data, we found out that pupils, who read syllables, made significantly more mistakes in individual cognitive functions – auditory classification, auditory differentiation, auditory memory, visual classifi cation, two-dimensional spatial orientation, visual and auditory perception of chronology and time, according to statistics. As noted above, one can assume that targeted stimulation of a reading method requires developing purposely the introduced areas of partial functions in the cognitive processes in the educational process.
Keywords: Research; Statistics as Topic; Female; dítě; statistika jako téma; kognitivní poruchy; ženské pohlaví; analýza metody čtení; výzkum; integrovaná výuka; lidé; Persons with Intellectual Disabilities; Teaching; školy; kognitivní funkce; Education; Schools; Cognition Disorders; Male; Reading; výchova a vzdělávání; vyučování; Child; mužské pohlaví; čtení; Mainstreaming, Education; osoby s mentálním postižením; Humans